Analisis SWOT Untuk Merumuskan Strategi Pemasaran Pada Usaha Mikro, Kecil dan Menengah Locy Cahaya Bersaudara Menggunakan Matriks IFAS, EFAS, SFAS, dan Grand Strategy - Eka Santi Agustina (JURNAL BISNIS DAN PEMBANGUNAN, 2024)
Abstract: The research method employed in this study is descriptive qualitative research. Data collection was conducted through interviews, observations, and documentation methods. The data analysis method employed in this study is SWOT analysis, conducted using EFAS and IFAS calculations. This involves examining Strengths, Weaknesses, Opportunities, and Threats. Results from research can be obtained by conducting a SWOT analysis based on EFAS and IFAS, followed by calculations using AFE and IFE. The analysis reveals the most significant internal factor, the secret recipe, with a weight of 0.3 and a scale of 9, and the least significant internal factor, irregular parking, with a weight of 0.1 and a scale of 2, totaling 6.7. The most dominant external factor, support from the local government, has a weight of 0.3 and a scale of 8, while the least significant external factors, scarcity of raw materials and competition, each have a weight of 0.1 and a scale of 3, totaling 6.4. Based on the SWOT correlation diagram, Locy Cahaya Bersaudara is in quadrant 2. Despite facing threats, the company has internal strengths. The strategy to be implemented is to capitalize on these strengths to pursue long-term opportunities through diversification. This involves making advancements in new activities by leveraging the company's internal strengths